2015
DOI: 10.5194/bg-12-3225-2015
|View full text |Cite
|
Sign up to set email alerts
|

Ideas and perspectives: on the emission of amines from terrestrial vegetation in the context of new atmospheric particle formation

Abstract: Abstract. In this article we summarise recent science which shows how airborne amines, specifically methylamines (MAs), play a key role in new atmospheric particle formation (NPF) by stabilising small molecule clusters. Agricultural emissions are assumed to constitute the most important MA source, but given the short atmospheric residence time of MAs, they can hardly have a direct impact on NPF events observed in remote regions. This leads us to the presentation of existing knowledge focussing on natural veget… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 129 publications
0
27
0
Order By: Relevance
“…Moreover, marine amines (ON) in the gas phase are here considered to form amine salts (ON in the particulate phase) consistent with the ON characterization by Altieri et al (2012) as predominantly containing reduced nitrogen. Amines of continental origin are not considered here because of the uncertainty and the weakness of their sources both of human and natural origin (Schade and Crutzen 1995;Ge et al 2011;Karl et al 2014;Sintermann and Neftel 2015). The organic nitrates that are of secondary origin and oxygenated inorganic nitrogen compounds both in the gas and particulate phases are explicitly calculated (Myriokefalitakis et al 2011).…”
Section: Methodology-model Descriptionmentioning
confidence: 99%
“…Moreover, marine amines (ON) in the gas phase are here considered to form amine salts (ON in the particulate phase) consistent with the ON characterization by Altieri et al (2012) as predominantly containing reduced nitrogen. Amines of continental origin are not considered here because of the uncertainty and the weakness of their sources both of human and natural origin (Schade and Crutzen 1995;Ge et al 2011;Karl et al 2014;Sintermann and Neftel 2015). The organic nitrates that are of secondary origin and oxygenated inorganic nitrogen compounds both in the gas and particulate phases are explicitly calculated (Myriokefalitakis et al 2011).…”
Section: Methodology-model Descriptionmentioning
confidence: 99%
“…Pollen could also contribute to OC because of its large size. Amines are another source of OC, but not well studied (Sintermann and Neftel, 2015). These sources from various sectors need to be further characterized for an unambiguous understanding of the sources of forest aerosols.…”
Section: Oc Fractions From Fungal Spores and Bvoc Oxidationmentioning
confidence: 99%
“…Certain PBAPs showed close correlations with atmospheric cloud condensation nucleus (CCN) and ice nucleus (IN) (Hiranuma et al, 2015;Huffman et al, 2013). However, simulations indicated that PBAPs are of regional importance for IN formation as they contribute very little to global average ice nucleation rates (Hoose et al, 2010;Spracklen and Heald, 2014). Unveiling PBAP mass concentrations is necessary to provide benchmarks for simulating its nucleation potentials and the effect on the climate.…”
Section: Introductionmentioning
confidence: 99%
“…Plants can emit a vast number of nitrogenous compounds to the atmosphere, which is known to affect atmospheric secondary aerosol formation and climate (Sintermann and Neftel, 2015). These compounds are formed in metabolic processes such as the decarboxylation and transamination of amino acids (Bagni and Tassoni, 2001;Dudareva et al, 2013).…”
Section: Potential Mechanisms For the Observed Intra-plant δ 15 N-n Amentioning
confidence: 99%
“…However, it is a widely established fact that leaves exchange NH 3 with atmosphere through stomata Wetselaar and Farquhar, 1980;Farquhar et al, 1983;Sharpe and Harper, 1997;Johnson and Berry, 2013;Flechard et al, 2013;Sintermann and Neftel, 2015). So for the momentum, let us focus on leaves (Figs.…”
Section: Potential Mechanisms For the Observed Intra-plant δ 15 N-n Amentioning
confidence: 99%